Seleksi Aktinomisetes Penghasil Protease dari Tanah Gambut Desa Langkai, Siak, Riau - LINDA, TETTY MARTA; MARTINA, ATRIA; FEBRIANTI, BERNADETA LENI; , HERLINDA; , TABRI (Jurnal Riau Biologia, 2016)
Actinomycetes is well known as secondary metabolites producer and hence it has high pharmacological andcommercial interest. In this study, a total of 14 isolates of actinomycetes from peat soils in Langkai Village,Siak, Riau had been selected for their ability to produce protease. Extracellular protease from Actinomycetesisolates was characterized by incubating the isolate in Nutrient Agar media containing casein 1%. Screeningof actinomycetes isolates showed that five isolates had the ability to produce a clear zone with the value ofproteolytic index (IP) ranged from 5.73 to 11.15. Isolates L313 showed the highest IP value (11.15), as wellas the highest protease production (0.041 U/ml) in Nutrient Broth media containing casein 1% after 6 daysincubation at room temperature.Key words: actinomycetes, clear zone, peat soil, protease, proteolitic index